Analisis Tingkat Kebisingan Stasiun Kereta Api (Studi Kasus Di Stasiun Madiun Dan Yogyakarta) - Istiantara, Dedik Tri (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
Noise control must be carried out as to reduce the noise level to the level specified according to the standard for a particular environment, for example a train station. The purpose of this study was to determine the relationship of noise intensity with work stress levels to employees at PT Kereta Api Indonesia (Persero), to measure noise intensity at Madiun Station and Yogyakarta, and to analyze work stress levels. experienced by employees. The results show that the noise value has exceeded the threshold value (NAV) determined by Kep-51 / MEN / 1999 and OSHA Standards, which is 85 dBA at 8 hours / day working hours which is in the range of 86.21 - 96.35 dBA , this noise level was received by 34 employees or 54.9%, while employees who were not exposed to noise under NAV were 26 people or 45.1%. The results also showed that the noise intensity at Yogyakarta Station was higher than at Madiun Station.